Migration and Climate Change in Latin America and the Caribbean - Kaenzig, Raoul; Piguet, Etienne (My University, 2014)
This literature overview aims to review the relationship between climate change and migration, with a special focus on Latin America and the Caribbean. After a brief history of the debate raised by the relationship between the environment and migration, we identify the main environmental consequences of climate change. In particular, we address the aspects related to tropical storms and hurricanes, floods, droughts, rising sea levels, and, melting glaciers. The paper then proceeds mainly by historical analogy: a summary of the past consequences for migration of these environmental degradations allows us to identify the most important migration issues related to climate change.
Keywords: Climate Change; Tropical Cyclone; Soil Erosion; Intergovernmental Panel; Tropical Storm